Sustainability of ecotourism resources at Taman Negara National Park: contingent valuation method - Samdin, Zaiton; Abdul Aziz, Yuhanis; Radam, Alias; Yacob, Mohd Rusli (Faculty of Economics and Business, Universiti Malaysia Sarawak, 2013)
This paper applies dichotomous choice Contingent Valuation Method to access the net economic values of ecotourism resources in Taman Negara National Park (TNNP). Based on the estimation results, equivalent Willingness to Pay (WTP) measures were calculated using logit and probit models. The calculated mean WTP ranged from RM11.01 to RM18.27 for the logit model, and for the probit model ranged from RM19.00 to RM30.32. The probit model performed slightly better than logit model in terms of McFadden R2. Therefore, the mean WTP obtained from the probit model would be a more reliable measure; RM23.36. Thus, estimation of the net benefit of TNNP for the year 2009 for visitors of 86,674 is RM2,024,704.64. This study also shows that visitors are willing to pay more for entrance permit; compared to current entrance permit (RM1). The implication of this study is important as a guideline to assist policy makers in terms of welfare measures such as recreational benefits and design an effective pricing policy at TNNP. For TNNP, the result of this study also provides an economic ground for its management’s effort as well as the policy makers’ decision to continue maintaining the area as a national park; thus one that will make a contribution to the long-term sustainable development of ecotourism areas.